KONSTRUKSI PEMAKNAAN TINDAK PIDANA KORUPSI MELALUI PENDEKATAN HERMENEUTIK - Ino Susanti (Masalah-Masalah Hukum, 2014)
Corruption Eradication Commission as the state agency have problems in the determination of corruption, especially in meaning among law enforcement. The problem occurs the meaning used only incompliance with the formalelements of the offense provisions set instatute. The purpose of this study is to reveal how the meaning and concept of Justice in dealing with corruption cases. The results showed construction of the meaning of corruption to justice must be based on people-oriented approach to living law (worth Pancasila) by sliding the fulfillment of the principle of legality stand point formal point of view to the legality which is material